PELATIHAN ASET TETAP BAGI SISWA/I SMA KRISTEN YUSUF JAKARTA - Amin Wijoyo; Adrian Martinus Hartono; Clara Felixa Tridian (Jurnal Serina Abdimas, 2026)
This Community Service Program (PKM) was conducted with the primary objective of enhancing financial literacy and deepening students’ understanding of basic accounting concepts, particularly the accounting equation and fixed asset management, among students of SMA Kristen Yusuf Jakarta. Understanding accounting from an early stage plays a crucial role in developing analytical, logical, and critical thinking skills that are essential for making sound economic decisions in the future. Based on preliminary observations, it was found that most students showed a strong interest in economics; however, they still faced challenges in comprehending financial transaction recording processes and financial statement analysis, which are fundamental to assessing an entity’s financial condition. The activity was conducted in person for 100 minutes and consisted of several stages: a pre-test, interactive material delivery, a quiz using the Kahoot platform, and a post-test to evaluate students’ comprehension. The materials covered the introduction of the entity concept, the accounting equation, and accounting treatment for fixed assets in financial statements. The evaluation results indicated a significant improvement in participants’ understanding, as evidenced by 78% of students correctly answering the post-test questions. Beyond enhancing academic competence, the program successfully increased students’ learning motivation, encouraged active participation, and created a fun and engaging learning atmosphere. Overall, this PKM activity is expected to serve as an effective learning model for strengthening financial literacy and critical thinking skills among high school students. Kegiatan Pengabdian kepada Masyarakat (PKM) ini dilaksanakan dengan tujuan utama untuk meningkatkan literasi keuangan serta memperdalam pemahaman siswa/i SMA Kristen Yusuf Jakarta terhadap konsep dasar akuntansi, khususnya mengenai persamaan dasar akuntansi dan pengelolaan aset tetap. Pemahaman akuntansi sejak usia sekolah menengah memiliki peran penting dalam membentuk kemampuan berpikir analitis, logis, dan kritis yang dibutuhkan untuk pengambilan keputusan ekonomi yang tepat di masa mendatang. Berdasarkan hasil observasi awal, ditemukan bahwa sebagian besar siswa menunjukkan minat yang tinggi terhadap bidang ekonomi, namun masih mengalami kendala dalam memahami proses pencatatan transaksi keuangan serta analisis laporan keuangan yang menjadi dasar penilaian kondisi keuangan suatu entitas. Pelaksanaan kegiatan dilakukan secara tatap muka selama 100 menit melalui beberapa tahapan, yaitu pre-test, penyampaian materi secara interaktif, kuis menggunakan platform Kahoot, serta post-test untuk mengevaluasi tingkat pemahaman peserta. Materi yang disampaikan meliputi pengenalan konsep entitas, persamaan akuntansi, serta perlakuan akuntansi terhadap aset tetap dalam laporan keuangan. Berdasarkan hasil evaluasi, kegiatan ini menunjukkan peningkatan yang signifikan terhadap pemahaman peserta, di mana 78% siswa mampu menjawab pertanyaan dengan benar pada post-test. Selain memberikan peningkatan kompetensi akademik, kegiatan PKM ini juga berhasil menumbuhkan motivasi belajar, semangat partisipasi aktif, serta menciptakan suasana pembelajaran yang menyenangkan dan interaktif. Secara keseluruhan, kegiatan ini diharapkan dapat menjadi model pembelajaran efektif dalam memperkuat literasi keuangan dan keterampilan berpikir kritis bagi siswa di tingkat sekolah menengah.